2011
DOI: 10.2106/jbjs.j.01325
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Patient Comprehension of Informed Consent

Abstract: Patient comprehension and recall immediately following a thorough discussion of the consent form was unexpectedly low. This poor recall deteriorated further between the preoperative visit and the first postoperative visit (a period of no more than two weeks). Greater age and lower education level were associated with poorer comprehension. Sex did not affect any of the scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 4 publications
2
47
2
1
Order By: Relevance
“…In a prospective evaluation of patient comprehension of informed consent, Crepeau et al. found that surgical patient comprehension and recall immediately following a thorough discussion of the consent form was unexpectedly low . Previous investigations have examined the readability of consent forms use in research protocols as a contributing factor to poor comprehension .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective evaluation of patient comprehension of informed consent, Crepeau et al. found that surgical patient comprehension and recall immediately following a thorough discussion of the consent form was unexpectedly low . Previous investigations have examined the readability of consent forms use in research protocols as a contributing factor to poor comprehension .…”
Section: Introductionmentioning
confidence: 99%
“…3 In a prospective evaluation of patient comprehension of informed consent, Crepeau et al found that surgical patient comprehension and recall immediately following a thorough discussion of the consent form was unexpectedly low. 4 Previous investigations have examined the readability of consent forms use in research protocols as a contributing factor to poor comprehension. [5][6][7] These research protocol consent forms are substantially different from consent forms used in daily clinical practice, and to our knowledge, no study has evaluated the readability of invasive procedure consent forms used in daily practice.…”
Section: Introductionmentioning
confidence: 99%
“…The level of recall of surgical complications was unrelated to sex; however, bettereducated patients were better at recalling the potential risks of an operation (11,15,18).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies of informed consent in clinical trials have that found some patients have limited understanding of the content presented during the consent process (Breese et al 2007; Crepeau et al 2011; Hill et al 2008; Joffe et al 2001). In response, researchers have proposed alternative methods, including cognitive interviewing techniques, visual aids, culturally appropriate resources, and attention to the oral presentation of the informed consent process’s key elements (Breese et al 2007; Yates et al 2009).…”
mentioning
confidence: 99%